Clinical Profile of Suspected and Confirmed COVID-19 Pneumonia Patients Admitted in a Tertiary Care Hospital, Sylhet, Bangladesh - Deb, Bidith Ranjan; Dev, Archana; Begum, Momtaz; Chowdhury, Sadia Malik (Jalalabad Medical Journal, 2025)
Coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-COV-2) has been declared a pandemic by the World Health Organization (WHO) with increasing morbidity and mortality. This cross-sectional study on 408 patients with suspected and confirmed COVID-19 pneumonia was conducted at the isolation ward for COVID-19 patients at Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, from October 2020 to December 2020. Their RT-PCR test was done from the designated laboratory and 48 of them were confirmed to be COVID-19 patients. The detailed demographics and clinical outcomes of the suspected and confirmed patients were analyzed. The mean age was 59±25 in the confirmed group and 56±15 in the negative group. The majority of the confirmed and suspected COVID-19 patients were between the ages of 61 and 70 (27.1% and 25.8%, respectively). Most of the patients were male, both in the confirmed (58.3%) and in the suspected group (53.6%). Fever, cough, dyspnoea, fatigue, headache, anorexia, and sore throat were common in both the suspected and confirmed groups, but dyspnoea (66.7%, p=0.0001), headache (33.3%, p=0.018), vomiting (33.3%, p=0.001), and sore throat (16.7%, p=0.002) were more frequently reported in the confirmed patients group than in the suspected patients. Fewer patients had COPD in the COVID-19 positive group than in the negative group (8.3% vs 26.7%, p=0.009), but diabetes mellitus was more common in the confirmed group than the suspected group (66.7% vs 48.9%, p=0.030). There were no significant differences in a range of other comorbidities, including hypertension (66.7% vs 56.8%, p=0.308), cerebrovascular disease (10.42% vs 13.3%, P=0.73), and asthma (16.7% vs 14.4%, p=0.848) in the confirmed and suspected groups. On the patient’s blood test, reduced WBC count was more common in the confirmed group than in the suspected group (16.7% vs 2.2%, p=0.000). C-reactive protein (CRP) levels were above normal in 48 (100%) of confirmed patients and 333 (92.2%) of suspected patients, which was not statistically significant (p=0.089). However, D-Dimer (100% vs 78.9%, p=0.000), Serum Ferritin (100% vs 78.9%, p=0.000), and Serum ALT (100% vs 51.1%, p=0.000) levels were significantly higher in the COVID-19 positive group. On CXR, bilateral consolidation was more common in the COVID-19 positive group than the COVID-19 negative group (83.3% vs 42.2%, p=0.000), whereas unilateral consolidation was more common in the suspected group than the confirmed group (38.9% vs 0%, p=0.000). On high resolution computed tomography (HRCT), ground glass opacities (GGO) were more common in confirmed patients than suspected patients (95% vs 55%, p=0.04). A higher proportion of patients with COVID-19 positive were referred to COVID dedicated hospitals than COVID negative patients (66.7% vs 5.6%, p=0.000). Sixteen (33.3%) of confirmed patients were discharged with advice. No death was observed in the confirmed group and 1.9% patients died in the suspected group. The maximum COVID-19 patients were aged over 60 and male. Typical presentations were fever, cough, dyspnoea, fatigue, anorexia, headache, vomiting, and sore throat, common in both confirmed and suspected groups. Hypertension and diabetes mellitus were the most common comorbidities. In confirmed COVID 19 patients, reduced WBC count and high CRP, Serum Ferritine, D-dimer, and Serum ALT were common laboratory findings, and bilateral consolidation on chest X-ray and ground glass opacities in HRCT were common radiological findings. Jalalabad Med J 2022; 19 (1): 11-20